PENGARUH PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP KARAKTER SISWA FASE C - Ricki, Ricki; Hamzah, Rahma Ashari; Maulidnawati, Abrina (ALENA : Journal of Elementary Education, 2025)
Character education is a key focus in Indonesia's education system, aimed at shaping a generation with integrity, responsibility, and personality in line with Pancasila values. The Pancasila Learner Profile Strengthening Project integrates these values into learning, fostering students who are faithful, pious, cooperative, creative, independent, and critical thinkers. However, challenges such as the influence of technology, environmental factors, and inconsistent application of Pancasila values hinder character development. This study evaluates the effectiveness of the Pancasila Learner Profile Strengthening Project in shaping student character, addressing the need for relevant learning innovations within the Merdeka Curriculum. The research uses an ex-post facto design with a quantitative approach, involving 27 fifth-grade students SDN 12 Kodeoha. Data collection methods include observation sheets, questionnaires, and documentation, analyzed through descriptive and inferential techniques. The findings show that the Pancasila Student Profile Project is still a new initiative at SDN 12 Kodeoha. Four key character dimensions were identified in the students: faith, piety, noble character, independence, creativity, and mutual cooperation. The students often demonstrate a sense of togetherness and social responsibility, helping each other in group assignments or projects. Hypothesis testing showed a significant effect of the project on student character, with a significance value of 0.001 <0.05, confirming the program’s positive influence on character development.